Process for the preparation of green plasticizer resin compositions
Patent Information
- Application Number
- CN202611185307.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-08-06
- Publication Date
- 2026-10-27
AI Technical Summary
[0005]本发明旨在解决基于内源性两亲性介质构建增塑体系与树脂基体间的动力学自锁网络,从而抑制增塑剂析出并提升组合物长期服役稳定性的问题
[0044](1)在绿色增塑剂树脂组合物的制备中,针对高分子树脂共混体系中极性各异的增塑剂组分存在的热力学相分离趋向,通过对连续酯化工序中反应深度的精确中止,使主增塑剂产物中原位截留占混合物总质量0.2%~0.8%的半酯化中间态寡聚物,该寡聚物作为两亲性拓扑钉扎介质,通过其一端的极性羟基或羧基与树脂基体极性区域建立强氢键锚定,并通过另一端的非极性长链脂肪烃穿透并物理缠结于主增塑剂与树脂基体的非晶区自由体积中,这种在组合物微观相界面处构建的动力学自锁结构,有效阻断增塑剂分子在长期服役过程中的差异化热力学迁移路径,从物理机制上解决树脂组合物表面析出及渗油问题;
Smart Images

Figure CN122978611A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of polymer compound composition technology, and particularly to a method for preparing a green plasticizer resin composition. Background Technology
[0002] Currently, fatty acid methyl esters derived from industrial oils are commonly used in combination with chlorinated paraffin as a composite plasticizer system to prepare green and environmentally friendly polymer resin compositions. This composite system aims to meet environmental regulations while balancing cost and flame retardant properties of the material through the synergistic effect between the components. However, there is a significant polarity gradient difference in the molecular structure between fatty acid methyl esters and chlorinated paraffin with high chlorine content. When this composite plasticizer system is blended into a polymer resin matrix, the thermodynamic incompatibility between the components during the cooling process after processing or the aging process during long-term service will cause differential migration of plasticizer molecules. This micro-phase separation phenomenon will inevitably cause the plasticizer components to accumulate on the material surface, resulting in physical defects such as oil seepage, precipitation, and material hardening.
[0003] To suppress plasticizer precipitation, conventional methods include adding exogenous macromolecular compatibility agents or improving product purity by enhancing esterification reaction conditions. However, the addition of exogenous compatibility agents significantly increases the melt viscosity of the composition, slows down the plasticization rate of the resin, and increases preparation costs. On the other hand, the pursuit of high-purity esterification processes eliminates amphiphilic oligomers with interfacial modulation potential originally present in the product, causing the interfacial tension between the primary and secondary plasticizers to lose its internal compensation mechanism. This technical trade-off between ensuring component compatibility and maintaining processing rheological properties is currently a physical bottleneck in this field. For example, patent document with publication number "CN119742111A" discloses a migration-resistant, environmentally friendly flexible PV. C-sheathed cables incorporate polyacrylate-based phthalate molecularly imprinted microspheres into the PVC sheath layer. These microspheres specifically bind and restrain plasticizer molecules, reducing their migration. However, the introduction of exogenous macromolecular imprinted microspheres can lead to stress concentration at the system's phase interface, increasing the melt viscosity of the composition and negatively interfering with the rheological behavior of large-scale continuous extrusion plasticization. Furthermore, the inherent difference in elastic modulus between the exogenous microspheres and the matrix resin can induce microcracks or new free volume cavities at the interface under thermal cycling or complex environmental stress. Under specific kinetic conditions, this accelerates the microscopic permeation of plasticizer molecules in the non-anchored region. Currently, this field relies on external intervention to capture molecules, neglecting the technological bottleneck of establishing a kinetic self-locking steady state from the in-situ reconstruction of endogenous components.
[0004] Therefore, the technical problem to be solved by this invention is how to utilize the endogenous components generated in the esterification process to construct a kinetically self-locking topological network in the resin matrix, thereby improving the composition's anti-precipitation performance and optimizing processing stability without introducing exogenous compatibility agents. Summary of the Invention
[0005] The present invention aims to solve the problem of constructing a kinetic self-locking network between the plasticizing system and the resin matrix based on an endogenous amphiphilic medium, thereby inhibiting plasticizer precipitation and improving the long-term service stability of the composition.
[0006] The technical solution of the present invention: a method for preparing a green plasticizer resin composition, comprising the following steps,
[0007] (S1) Prepare an ester-based main plasticizer containing amphiphilic semi-esterified oligomers;
[0008] The preparation in step (S1) is as follows:
[0009] (S1-1) Industrial oils with an inlet temperature of 115℃~125℃ are introduced into the reaction system with methanol, and continuous esterification is carried out at a temperature of 110℃~130℃, which can be adapted to the continuous esterification of industrial oils with various acid values; more preferably, industrial oils with an inlet temperature of 118℃~123℃ are introduced into the reaction system with methanol, and continuous esterification is carried out at a temperature of 115℃~125℃, which can balance esterification efficiency and oil oxidation inhibition; even more preferably, industrial oils with an inlet temperature of 120℃ are introduced into the reaction system with methanol, and continuous esterification is carried out at a temperature of 120℃, which can be adapted to industrial oils with an acid value of 2~3;
[0010] (S1-2) The methanol vapor phase temperature in the reaction system of step (S1-1) is controlled within the range of 120°C to 140°C as the esterification termination depth, so that the in-situ retained amphiphilic hemiesterified oligomers in the ester main plasticizer account for 0.2% to 0.8% of the total mass of the ester main plasticizer; more preferably, the methanol vapor phase temperature in the reaction system of step (S1-1) is controlled within the range of 125°C to 135°C as the esterification termination depth, so that the in-situ retained amphiphilic hemiesterified oligomers in the ester main plasticizer account for 0.3% of the total mass of the ester main plasticizer. ~0.7%; more preferably, the methanol vapor phase temperature in the reaction system of step (S1-1) is controlled within the range of 128°C to 132°C as the esterification termination depth, so that the in-situ retained amphiphilic semi-esterified oligomers in the ester main plasticizer account for 0.4% to 0.6% of the total mass of the ester main plasticizer; more preferably, the methanol vapor phase temperature in the reaction system of step (S1-1) is controlled within the range of 130°C as the esterification termination depth, so that the in-situ retained amphiphilic semi-esterified oligomers in the ester main plasticizer account for 0.5% of the total mass of the ester main plasticizer;
[0011] (S2) Prepare an auxiliary plasticizer containing residual free hydrogen chloride;
[0012] (S3) Take polymer resin, antioxidant and stabilizer, and mix them with the ester main plasticizer in step (S1) and the auxiliary plasticizer in step (S2) in a preset ratio into the mixing system to obtain resin mixture;
[0013] (S4) The resin mixture from step (S3) is heated to above the glass transition temperature of the polymer resin. Residual free hydrogen chloride induces interfacial anchoring at the polar ends of the amphiphilic semi-esterified oligomers, forming a secondary bond network with the co-plasticizer and functional groups of the polymer resin. A kinetically self-locking structure is constructed in the free volume of the amorphous region of the polymer resin, thus obtaining a green plasticizer resin composition. During the mixing stage, only the PVC stabilizer is preheated to 60–80°C, below the PVC glass transition temperature T. At g=80~85℃, the stabilizer does not come into contact with free HCl. The plasticizer is added at low temperature and premixed before being fed into the extruder. The temperature of the pre-plasticizing section at the front end of the extruder is 90~110℃, which exceeds Tg. HCl induces the oligomer orientation and builds a secondary bond network. The temperature at the middle and rear ends is raised to 160~170℃ for plasticization. Calcium and zinc stabilizers are added to the feed at the rear to neutralize excess HCl and prevent thermal degradation of PVC. The screw shear field, combined with the segmented temperature, can achieve the sequence of first polarization anchoring and then stabilization and acid removal, ensuring the complete molding of the self-locking structure.
[0014] The kinetic self-locking structure is that one end of the amphiphilic semi-esterified oligomer is hydrogen-bonded to the polar groups of PVC or chlorinated paraffin, and the other end is a long chain entangled with the free volume of the amorphous region of PVC to form a micro-network that restricts the migration of plasticizer.
[0015] Amphiphilic semi-esterified oligomers are generated from incomplete transesterification of industrial oils and fats, and are mixtures of oligoglycerol esters containing both polar hydroxyl or carboxyl termini and nonpolar long-chain fatty acids. The characterization and quantitative detection methods for these amphiphilic semi-esterified oligomers are as follows: The amphiphilic semi-esterified oligomers are mainly composed of diglycerol monoesters and triglycerol diesters, with a degree of polymerization of 2–3. Quantitative detection was performed using high-performance liquid chromatography (HPLC) with a C18 column, methanol-water gradient elution, and an evaporative light scattering detector. The esterified main plasticizer sample was diluted to 10 mg / mL, and 20 μL was injected. The oligomer mass fraction was calculated using the external standard method, confirming it to be in the range of 0.2–0.8%.
[0016] The amphiphilic topological pinning medium is an amphiphilic semi-esterified oligomer generated in situ during the esterification process of this invention. One polar end is anchored to the resin or co-plasticizer by hydrogen bonds, while the other end has long chains that entangle the free volume of PVC, physically restraining the migration of plasticizer.
[0017] This invention creates stable and efficient reaction conditions for the transesterification reaction of fatty acid methyl esters by precisely controlling the feed and reaction temperature of industrial oils, whose main component is triglycerides, and methanol. Under limited temperature, the reaction rate is moderate, and the catalyst activity is good, avoiding side reactions such as oil oxidation and polymerization or excessive methanol vaporization caused by excessive temperature. By monitoring and controlling the vapor phase temperature of methanol in the reactor, a specific proportion of amphiphilic semi-esterified oligomers is retained, rather than pursuing complete conversion of the esterification reaction. Precise control of the methanol vapor phase temperature indirectly controls the methanol concentration and reaction progress within the reaction system. When the reaction proceeds to a certain extent, some glycerides are not completely converted to methyl esters, but instead generate semi-esterified oligomers with one polar and one nonpolar end. This invention blends a main plasticizer containing amphiphilic oligomers, a co-plasticizer containing residual HCl, and components such as PVC resin, and, at a temperature higher than the glass transition temperature of PVC, utilizes the shear field of a twin-screw extruder to trigger a series of synergistic effects, forming a stable internal network. Fatty acid esters are the main plasticizer. The plasticizer and chlorinated paraffin co-plasticizer initially function as traditional plasticizers, inserting themselves between PVC molecular chains to weaken intermolecular forces, lower Tg, and improve processing fluidity. Upon heating, the residual free HCl, as a highly polar substance, preferentially interacts strongly with the polar ends of the amphiphilic hemiesterified oligomers, inducing them to migrate and align at the plasticizer-resin interface. The induced amphiphilic oligomers, through the bridging effect of HCl, form secondary groups with the polar functional groups of the chlorinated paraffin co-plasticizer and PVC resin. The bond network, at the same time, its nonpolar long chain ends are deeply embedded in the free volume of the amorphous region of PVC like anchors. This structure, with one end anchored at the interface and the other end locked in the free volume, restricts the long-range migration of plasticizer molecules in the PVC matrix. Since this structure is formed by the in-situ reaction of each component during processing, it is called a kinetic self-locking structure. Its direct effect is to greatly improve the permanence of plasticizers, which is manifested in the fact that after being placed at 70°C for 168 hours, the surface oil penetration level reaches the highest level 0, that is, no penetration.
[0018] Preferably, the industrial oil is a plant-based crude triglyceride oil, such as soybean oil, rapeseed oil, palm oil, or refined oil recycled from catering. The industrial oil has an acid value of 2.0–4.0 mg KOH / g, moisture ≤0.1 wt%, gum ≤0.05 wt%, and iodine value of 90–130 g I2 / 100g. If the oil acid value is <2, the esterification conversion rate of glycerides will be too high, and sufficient amphiphilic hemiesterified oligomers cannot be retained. If the acid value is >4, the oil is prone to high-temperature oxidation, producing colored impurities and deteriorating the resin transparency and aging resistance. In this example, soybean oil with an acid value of 2.5 is preferred.
[0019] Preferably, an alkaline transesterification catalyst is added to the esterification reaction in step (S1-1).
[0020] Preferably, the alkaline transesterification catalyst is selected from sodium methoxide, sodium hydroxide, or potassium hydroxide; the amount of alkaline transesterification catalyst added is 0.3–0.8 wt% based on the mass of industrial oil. More preferably, the amount of alkaline transesterification catalyst added is 0.4–0.7 wt%. Even more preferably, the amount of alkaline transesterification catalyst added is 0.5–0.6 wt%. The alkaline transesterification catalyst is prepared into a 20 wt% methanol solution and simultaneously and continuously fed into the primary esterification reactor along with methanol. This provides catalytic activity stability, allows control over the esterification depth to retain semi-esterified oligomers, and avoids high-temperature side reactions.
[0021] Preferably, in step (S1-1), the inlet flow rate of the industrial grease is controlled to be 3.5 m³ / s. 3 / h~4.5m 3 The methanol inlet flow rate is controlled at 0.8 m³ / h. 3 / h~1.2m 3 / h. More preferably, the inlet flow rate of industrial grease is controlled at 3.7m. 3 / h~4.2m 3 The methanol inlet flow rate is controlled at 0.9 m³ / h. 3 / h~1.1m 3 / h. More preferably, the inlet flow rate of the industrial grease is controlled at 4m. 3 / h, control the methanol inlet flow rate to 1m³ / h. 3 / h. The limited oil and alcohol inlet flow rates ensure a constant reactant ratio, which is the foundation for guaranteeing product quality stability; a stable oil-alcohol molar ratio ensures a stable amount of semi-esterified oligomers formed.
[0022] Preferably, step (S1-2) involves continuous esterification in five esterification reactors connected in series. The concentration stability of the amphiphilic semi-esterified oligomer in the ester-based main plasticizer is maintained by adjusting the methanol gas flow rate and methanol gas pressure in each esterification reactor.
[0023] Preferably, in step (S1-2), the methanol gas flow rate is gradient-distributed in the five esterification reactors connected in series. The methanol gas flow rate corresponding to the first to fifth esterification reactors decreases sequentially: 160–180 m³ / h for the first stage, 150–170 m³ / h for the second stage, 140–160 m³ / h for the third stage, 130–150 m³ / h for the fourth stage, and 120–140 m³ / h for the fifth stage. The slight positive pressure inside the reactors is uniformly controlled at 0.02–0.05 MPa. 30%–40% of the methanol vapor is condensed and refluxed back into the reactor from the top of each stage, and excess methanol is uniformly recovered. The high-methanol content at the front end... The alcohol concentration promotes the formation of semi-esterified oligomers, while the low methanol concentration at the end avoids complete esterification and the consumption of oligomers. The reactor temperature is gradually increased in stages along the material flow direction, with the first stage reactor temperature at 110℃ and the fifth stage reactor temperature reaching a maximum of 130℃. Methanol gas phase is drawn out from the top of each stage reactor, and part of the methanol is returned to the reactor through the condenser, while excess methanol is collected and recovered. The methanol gas flow rate of each stage reactor decreases gradually. The high methanol concentration at the front end promotes the initial transesterification of oils and fats to form semi-esterified oligomers, while the low methanol concentration at the back end avoids complete esterification and the consumption of oligomers. Combined with the termination threshold of methanol gas phase temperature of 130℃, the mass percentage of oligomers is precisely locked at 0.2% to 0.8%.
[0024] Preferably, in step (S1), the mass percentage of the amphiphilic hemiesterified oligomer in the ester-based main plasticizer satisfies the formula... ,in, This represents the mass percentage of the amphiphilic hemiesterified oligomer. The mass of the amphiphilic semi-esterified oligomer in the system, This represents the total mass of the ester-based primary plasticizer after esterification, expressed as a percentage by mass. The value range is 0.2% to 0.8%.
[0025] Preferably, the preparation in step (S2) is as follows:
[0026] (S2-1) Control the chlorination of low-n-alkane liquid paraffin to obtain chlorinated paraffin product auxiliary plasticizer;
[0027] (S2-2) During the reaction process in step (S2-1), the vacuum degree of the negative pressure degassing process is adjusted to -0.08 MPa to -0.05 MPa, and the degassing time is controlled to be 15 min to 30 min, so as to retain residual free hydrogen chloride in situ in the auxiliary plasticizer. More preferably, during the reaction process in step (S2-1), the vacuum degree of the negative pressure degassing process is adjusted to -0.07 MPa to -0.06 MPa, and the degassing time is controlled to be 20 min to 25 min, so as to retain residual free hydrogen chloride in situ in the auxiliary plasticizer. More preferably, during the reaction process in step (S2-1), the vacuum degree of the negative pressure degassing process is adjusted to -0.065 MPa, and the degassing time is controlled to be 23 min, so as to retain residual free hydrogen chloride in situ in the auxiliary plasticizer. In the preparation of chlorinated paraffin, the vacuum degree and degassing time of the negative pressure degassing process are adjusted to prevent complete removal of HCl, leaving a portion of residual free HCl in the product. By precisely controlling the vacuum degree and time of degassing, most of the HCl is removed, while a small amount is intentionally retained. This residual HCl will serve as an initiator or catalyst for the next reaction. Offline samples are taken every 15 minutes during the degassing process, and free HCl is determined by silver nitrate potentiometric titration. When the measured value deviates from 50 ppm ± 5 ppm, the vacuum pump negative pressure is adjusted with a gradient of 0.005 MPa. When the viscosity of paraffin increases, the vacuum degree is appropriately increased to extend the degassing time; when the viscosity decreases, the vacuum degree is reduced to shorten the degassing time, maintaining a stable free HCl level of 45–55 ppm.
[0028] Preferably, in the chlorinated paraffin-52 after negative pressure degassing in step (S2-2), the free hydrogen chloride content is controlled at 45-55 ppm. More preferably, the free hydrogen chloride content is controlled at 50 ppm. Below 45 ppm, there will be insufficient polarization induction; above 55 ppm, it will cause slight thermal degradation of PVC during extrusion, resulting in yellowing of the product. The higher the vacuum degree and the longer the degassing time, the lower the residual HCl will be. When the viscosity of the raw material paraffin fluctuates, the free hydrogen chloride content is stably maintained in the range of 45-55 ppm by vacuum fine-tuning compensation of ±0.005 MPa.
[0029] Preferably, the detection method for free hydrogen chloride in step (S2-2) is silver nitrate potentiometric titration. Specifically, 10g of chlorinated paraffin sample is dissolved in 50mL of anhydrous ethanol, magnetically stirred for 10min, and potentiometrically titrated with 0.01mol / L silver nitrate standard solution. The mass concentration of free hydrogen chloride is calculated based on the volume consumed at the jump point.
[0030] Preferably, the chlorinated paraffin product co-plasticizer in step (S2-1) is chlorinated paraffin-52 with a chlorine content in the range of 50% to 54%; the reaction temperature for preparing the co-plasticizer is 80℃ to 103℃, and the reaction endpoint is determined based on the refractive index or density of the co-plasticizer. More preferably, it is chlorinated paraffin-52 with a chlorine content in the range of 51% to 53%; the reaction temperature for preparing the co-plasticizer is 85℃ to 100℃. Even more preferably, it is chlorinated paraffin-52 with a chlorine content in the range of 52%; the reaction temperature for preparing the co-plasticizer is 90℃ to 95℃.
[0031] Preferably, the polymer resin in step (S3) is polyvinyl chloride resin, the stabilizer is a calcium-zinc composite stabilizer, and the antioxidant is a hindered phenolic antioxidant or a phosphite antioxidant.
[0032] Preferably, in step (S3), the polymer resin and stabilizer are first preheated to 60°C–80°C under high-speed stirring, and then the ester-based primary plasticizer and secondary plasticizer are added. More preferably, the polymer resin and stabilizer are first preheated to 65°C–75°C under high-speed stirring. Even more preferably, the polymer resin and stabilizer are first preheated to 70°C under high-speed stirring.
[0033] Preferably, the green plasticizer resin composition comprises the following components in parts by weight:
[0034] The main plasticizer is 15 to 25 parts ester, the auxiliary plasticizer is 10 to 20 parts, the polymer resin is 50.5 to 72.8 parts, the antioxidant is 0.2 to 0.5 parts, and the stabilizer is 2 to 4 parts.
[0035] Preferably, the green plasticizer resin composition comprises the following components in parts by weight:
[0036] The main plasticizer is 18 to 22 parts ester, the auxiliary plasticizer is 12 to 18 parts, the polymer resin is 55 to 70 parts, the antioxidant is 0.3 to 0.4 parts, and the stabilizer is 2.5 to 3.5 parts.
[0037] Preferably, the green plasticizer resin composition comprises the following components in parts by weight:
[0038] 20 parts of ester-based primary plasticizer, 15 parts of secondary plasticizer, 62 parts of polymer resin, 0.35 parts of antioxidant, and 3 parts of stabilizer.
[0039] Preferably, the heating temperature in step (S4) is controlled between 155°C and 175°C. More preferably, the heating temperature is controlled between 160°C and 170°C. Even more preferably, the heating temperature is controlled at 165°C.
[0040] Preferably, the construction of the kinetic self-locking structure in step (S4) is completed in an extrusion molding apparatus, with the heating temperature of each zone of the extrusion molding apparatus set between 150°C and 185°C to trigger the interfacial anchoring of the amphiphilic semi-esterified oligomers while the resin mixture is plasticized. More preferably, the heating temperature of each zone of the extrusion molding apparatus is set between 155°C and 180°C. More preferably, the heating temperature of each zone of the extrusion molding apparatus is set between 160°C and 175°C. More preferably, the heating temperature of each zone of the extrusion molding apparatus is set between 165°C and 170°C.
[0041] Preferably, the extrusion molding equipment is a co-rotating twin-screw extruder, and the screw speed of the co-rotating twin-screw extruder is controlled at 150 r / min to 300 r / min. The shear field, combined with residual free hydrogen chloride, causes the amphiphilic semi-esterified oligomers to align at the phase interface of the resin mixture. More preferably, the screw speed of the co-rotating twin-screw extruder is controlled at 200 r / min to 250 r / min. Even more preferably, the screw speed of the co-rotating twin-screw extruder is controlled at 220 r / min.
[0042] Preferably, after obtaining the green plasticizer resin composition, the process further includes cooling and granulating the green plasticizer resin composition, sieving, and packaging. The surface oil penetration grade of the obtained green plasticizer resin composition is grade 0 after being placed at 65°C to 75°C for 150 to 180 hours. More preferably, the surface oil penetration grade of the obtained green plasticizer resin composition is grade 0 after being placed at 68°C to 72°C for 160 to 170 hours. Even more preferably, the surface oil penetration grade of the obtained green plasticizer resin composition is grade 0 after being placed at 70°C for 168 hours.
[0043] The present invention has the following beneficial effects:
[0044] (1) In the preparation of green plasticizer resin composition, in view of the thermodynamic phase separation tendency of plasticizer components with different polarities in polymer resin blend system, by precisely stopping the reaction depth in the continuous esterification process, the semi-esterified intermediate oligomers accounting for 0.2% to 0.8% of the total mass of the mixture are retained in situ in the main plasticizer product. The oligomers, as amphiphilic topological pinning media, are anchored to the polar region of the resin matrix by establishing strong hydrogen bonds through the polar hydroxyl or carboxyl groups at one end, and penetrate and physically entangled in the free volume of the amorphous region of the main plasticizer and the resin matrix through the non-polar long-chain aliphatic hydrocarbons at the other end. This kinetic self-locking structure constructed at the micro-phase interface of the composition effectively blocks the differential thermodynamic migration path of plasticizer molecules during long-term service, and solves the problem of surface precipitation and oil seepage of resin composition from a physical mechanism.
[0045] (2) The trace amount of free hydrogen chloride retained in the negative pressure degassing process during the preparation of the auxiliary plasticizer is used as an in-situ polarization catalyst. During the process of mixing and heating the resin to above the glass transition temperature, it synergistically induces the polar end of the amphiphilic oligomer in the main plasticizer to generate an orientation polarization effect. This effect promotes the formation of a high-density secondary bond network between the polar end of the oligomer and the chlorine-rich segments in the auxiliary plasticizer and the functional groups of the resin matrix. This enables the main and auxiliary plasticizers, which originally had polarity gradient deviations, to achieve microscopic stability within the free volume of the resin. This interface reconstruction mediated by the endogenous polarization factor improves the processing rheological stability of the resin composition and avoids local embrittlement of the material caused by uneven component distribution in the physical blend system. Attached Figure Description
[0046] Figure 1 This is a flowchart illustrating the in-situ component retention and self-locking construction process of the green plasticizer resin composition involved in this invention;
[0047] Figure 2 This is a functional hierarchy and logical architecture diagram of the green plasticizer preparation system involved in this invention. Detailed Implementation
[0048] The technical solutions of the embodiments of this application will be clearly described below with reference to the accompanying drawings. Obviously, the described embodiments are only some embodiments of this application, not all embodiments. All other embodiments obtained by those skilled in the art based on the embodiments of this application are within the scope of protection of this application.
[0049] A method for preparing a green plasticizer resin composition includes the following steps:
[0050] (S1) Prepare an ester-based main plasticizer containing amphiphilic semi-esterified oligomers;
[0051] The preparation in step (S1) is as follows:
[0052] (S1-1) Industrial grease with an inlet temperature controlled at 115℃~125℃ and methanol are introduced into the reaction system, and esterification is carried out continuously at a temperature of 110℃~130℃; industrial grease with an inlet temperature controlled at 118℃~123℃ and methanol are introduced into the reaction system, and esterification is carried out continuously at a temperature of 115℃~125℃; industrial grease with an inlet temperature controlled at 120℃ and methanol are introduced into the reaction system, and esterification is carried out continuously at a temperature of 120℃; in step (S1-1), the inlet flow rate of industrial grease is controlled at 3.5m. 3 / h~4.5m 3 The methanol inlet flow rate is controlled at 0.8 m³ / h. 3 / h~1.2m 3 / h; control the inlet flow rate of industrial grease to 3.7m. 3 / h~4.2m3 The methanol inlet flow rate is controlled at 0.9 m³ / h. 3 / h~1.1m 3 / h; control the inlet flow rate of industrial grease to 4m 3 / h, control the methanol inlet flow rate to 1m³ / h. 3 / h;
[0053] In step (S1), the mass percentage of the amphiphilic semi-esterified oligomer in the ester-based main plasticizer satisfies the formula... ,in, This represents the mass percentage of the amphiphilic hemiesterified oligomer. The mass of the amphiphilic semi-esterified oligomer in the system, This represents the total mass of the ester-based primary plasticizer after esterification, expressed as a percentage by mass. The value range is 0.2% to 0.8%;
[0054] (S1-2) The methanol vapor phase temperature in the reaction system of step (S1-1) is controlled within the range of 120℃ to 140℃ as the esterification depth to be terminated, so that the in-situ retained amphiphilic semi-esterified oligomers in the ester main plasticizer account for 0.2% to 0.8% of the total mass of the ester main plasticizer; The methanol vapor phase temperature in the reaction system of step (S1-1) is controlled within the range of 125℃ to 135℃ as the esterification depth to be terminated, so that the in-situ retained amphiphilic semi-esterified oligomers in the ester main plasticizer account for 0.3% to 0.7% of the total mass of the ester main plasticizer; The methanol vapor phase temperature in the reaction system of step (S1-1) is controlled within the range of 128℃ to 132℃ as the esterification depth to be terminated, so that the in-situ retained amphiphilic semi-esterified oligomers in the ester main plasticizer account for 0.4% to 0.6% of the total mass of the ester main plasticizer; The methanol vapor phase temperature in the reaction system of step (S1-1) is controlled within the range of 120℃ to 140℃ as the esterification depth to be terminated, so that the in-situ retained amphiphilic semi-esterified oligomers in the ester main plasticizer account for 0.4% to 0.6% of the total mass of the ester main plasticizer; The methanol vapor phase temperature in the reaction system of step (S1-1) is controlled within the range of 125℃ to 135℃ as the esterification depth to be terminated, so that the in-situ retained amphiphilic semi-esterified oligomers in the ester main plasticizer account for 0.4% to 0.6% of the total mass of the ester main plasticizer; The methanol vapor phase temperature in the reaction system of step (S1-1) is controlled within the range of 1 The esterification depth is stopped at a temperature of 130℃, ensuring that the in-situ retained amphiphilic semi-esterified oligomers in the ester main plasticizer account for 0.5% of the total mass of the ester main plasticizer. Step (S1-2) involves continuous esterification in five esterification reactors connected in series. The concentration stability of the amphiphilic semi-esterified oligomers in the ester main plasticizer is maintained by adjusting the methanol gas flow rate and methanol gas pressure in each esterification reactor. In step (S1-2), the methanol gas flow rate is gradient-distributed in the five esterification reactors connected in series. The methanol gas flow rate corresponding to the first-stage esterification reactor to the fifth-stage esterification reactor decreases sequentially: 160-180 m³ / h for the first stage, 150-170 m³ / h for the second stage, 140-160 m³ / h for the third stage, 130-150 m³ / h for the fourth stage, and 120-140 m³ / h for the fifth stage. The micro-positive pressure inside the reactor is uniformly controlled at 0.02-0.05 MPa.
[0055] (S2) Prepare an auxiliary plasticizer containing residual free hydrogen chloride;
[0056] The preparation in step (S2) is as follows:
[0057] (S2-1) Controlled chlorination of low-n-alkane liquid paraffin yields chlorinated paraffin product co-plasticizer; the chlorinated paraffin product co-plasticizer in step (S2-1) is chlorinated paraffin-52 with a chlorine content in the range of 50% to 54%; the reaction temperature for preparing the co-plasticizer is 80℃ to 103℃, and the reaction endpoint is determined based on the refractive index or density of the co-plasticizer; chlorinated paraffin-52 with a chlorine content in the range of 51% to 53%; the reaction temperature for preparing the co-plasticizer is 85℃ to 100℃; chlorinated paraffin-52 with a chlorine content in the range of 52%; the reaction temperature for preparing the co-plasticizer is 90℃ to 95℃;
[0058] (S2-2) In the reaction process of step (S2-1), the vacuum degree of the negative pressure degassing process is adjusted to -0.08MPa to -0.05MPa, and the degassing time is controlled to be 15min to 30min, so as to retain residual free hydrogen chloride in situ in the auxiliary plasticizer; In the reaction process of step (S2-1), the vacuum degree of the negative pressure degassing process is adjusted to -0.07MPa to -0.06MPa, and the degassing time is controlled to be 20min to 25min, so as to retain residual free hydrogen chloride in situ in the auxiliary plasticizer; In the reaction process of step (S2-1), the vacuum degree of the negative pressure degassing process is adjusted to -0.065MPa, and the degassing time is controlled to be 23min, so as to retain residual free hydrogen chloride in situ in the auxiliary plasticizer.
[0059] (S3) Take the polymer resin, antioxidant, and stabilizer, and mix them with the ester-based primary plasticizer from step (S1) and the auxiliary plasticizer from step (S2) according to a preset ratio in the mixing system to obtain a resin mixture; the polymer resin in step (S3) is polyvinyl chloride resin, the stabilizer is calcium-zinc composite stabilizer, and the antioxidant is hindered phenolic antioxidant or phosphite antioxidant; in step (S3), the polymer resin and stabilizer are first preheated to 60℃~80℃ under high-speed stirring, and then the ester-based primary plasticizer and auxiliary plasticizer are added; the polymer resin and stabilizer are first preheated to 65℃~75℃ under high-speed stirring; the polymer resin and stabilizer are first preheated to 70℃ under high-speed stirring.
[0060] (S4) The resin mixture in step (S3) is heated to above the glass transition temperature of the polymer resin. The residual free hydrogen chloride induces the polar end of the amphiphilic semi-esterified oligomer to generate an interfacial anchoring effect, so that the polar end forms a secondary bond network with the co-plasticizer and the functional groups of the polymer resin, and constructs a kinetic self-locking structure in the free volume of the amorphous region of the polymer resin to obtain a green plasticizer resin composition.
[0061] The green plasticizer resin composition comprises the following components in parts by weight.
[0062] 15 to 25 parts of ester-based primary plasticizer, 10 to 20 parts of auxiliary plasticizer, 50.5 to 72.8 parts of polymer resin, 0.2 to 0.5 parts of antioxidant, and 2 to 4 parts of stabilizer;
[0063] The green plasticizer resin composition comprises the following components in parts by weight.
[0064] The main plasticizer is 18 to 22 parts ester, the auxiliary plasticizer is 12 to 18 parts, the polymer resin is 55 to 70 parts, the antioxidant is 0.3 to 0.4 parts, and the stabilizer is 2.5 to 3.5 parts.
[0065] The green plasticizer resin composition comprises the following components in parts by weight.
[0066] 20 parts of ester-based primary plasticizer, 15 parts of secondary plasticizer, 62 parts of polymer resin, 0.35 parts of antioxidant, and 3 parts of stabilizer;
[0067] In step (S4), the heating temperature is controlled at 155℃~175℃; the heating temperature is controlled at 160℃~170℃; the heating temperature is controlled at 165℃.
[0068] In step (S4), the construction of the kinetic self-locking structure is completed in the extrusion molding equipment. The heating temperature of each zone of the extrusion molding equipment is set at 150℃~185℃ to trigger the interfacial anchoring of the amphiphilic semi-esterified oligomer while plasticizing the resin mixture. The heating temperature of each zone of the extrusion molding equipment is set at 155℃~180℃; the heating temperature of each zone of the extrusion molding equipment is set at 160℃~175℃; the heating temperature of each zone of the extrusion molding equipment is set at 165℃~170℃.
[0069] The extrusion molding equipment is a co-rotating twin-screw extruder. The screw speed of the co-rotating twin-screw extruder is controlled at 150 r / min to 300 r / min. The shear field, combined with residual free hydrogen chloride, causes the amphiphilic semi-esterified oligomers to align at the phase interface of the resin mixture. The screw speed of the co-rotating twin-screw extruder is controlled at 200 r / min to 250 r / min. The screw speed of the co-rotating twin-screw extruder is controlled at 220 r / min.
[0070] After obtaining the green plasticizer resin composition, the process also includes cooling, granulating, sieving, and packaging the green plasticizer resin composition. The surface oil penetration grade of the obtained green plasticizer resin composition after being placed at 65℃~75℃ for 150h~180h is grade 0; the surface oil penetration grade of the obtained green plasticizer resin composition after being placed at 68℃~72℃ for 160h~170h is grade 0; and the surface oil penetration grade of the obtained green plasticizer resin composition after being placed at 70℃ for 168h is grade 0.
[0071] The test method for the grade of heat aging oil seepage is as follows: plasticizer migration test according to HG / T3831-2019 PVC; the sample is an extruded sheet with a thickness of 1 mm and a thickness of 50×50 mm; it is placed in a 70℃ forced-air oven for 168 hours, then taken out and cooled to room temperature for visual inspection and wiping with filter paper; the grading standard is: grade 0, no oil stains on the filter paper, no whitening and precipitation on the sample surface; grades 1 to 5, the oil stains are heavier in sequence; all embodiments of this invention reach grade 0; this test method is applicable to cables or general PVC materials;
[0072] The method for testing the mass loss rate under 70℃ heat aging is as follows: take 3 samples, weigh each sample precisely to an accuracy of 0.01mg, keep them at 70℃ for 168h, remove them, dry and cool them for 2h, and weigh them again; the mass loss rate = (initial total mass - total mass after aging) / initial total mass × 100%;
[0073] The sterilization and dissolution test methods for medical tubing are as follows: sterilization with saturated steam at 121℃ for 30 minutes; transmittance is measured using a UV-Vis spectrophotometer at a wavelength of 450nm for the transmittance of the tubing sheet; dissolution is measured after soaking in physiological saline at 37℃ for 240 hours, and the amount of fatty acid methyl esters and chlorinated paraffins dissolved in the soaking solution is detected by gas chromatography. If no methyl esters and chlorinated paraffins are detected, the product is considered qualified.
[0074] Example 1: A method for preparing a green plasticizer resin composition, comprising the following steps:
[0075] (S1) Prepare an ester-based main plasticizer containing amphiphilic semi-esterified oligomers;
[0076] The preparation in step (S1) is as follows:
[0077] (S1-1) Industrial grease with an inlet temperature controlled at 115℃ and methanol are introduced into the reaction system and continuously esterified at 110℃; in step (S1-1), the inlet flow rate of the industrial grease is controlled at 3.5m. 3 The methanol inlet flow rate is controlled at 0.8 m³ / h. 3 / h;
[0078] In step (S1), the mass percentage of the amphiphilic semi-esterified oligomer in the ester-based main plasticizer satisfies the formula... ,in, This represents the mass percentage of the amphiphilic hemiesterified oligomer. The mass of the amphiphilic semi-esterified oligomer in the system, This represents the total mass of the ester-based primary plasticizer after esterification, expressed as a percentage by mass. The value is 0.2%;
[0079] (S1-2) The methanol vapor phase temperature in the reaction system of step (S1-1) is controlled at 120℃ as the esterification depth to stop, so that the amphiphilic semi-esterified oligomers retained in situ in the ester main plasticizer account for 0.2% of the total mass of the ester main plasticizer; Step (S1-2) esterification is carried out continuously in five esterification reactors connected in series. The concentration stability of the amphiphilic semi-esterified oligomers in the ester main plasticizer is maintained by adjusting the methanol gas flow rate and methanol gas pressure of each esterification reactor; The methanol gas flow rate in step (S1-2) is gradient distributed in the five esterification reactors connected in series. The methanol gas flow rate corresponding to the first-stage esterification reactor to the fifth-stage esterification reactor decreases step by step, with the first stage at 160 m³ / h, the second stage at 150 m³ / h, the third stage at 140 m³ / h, the fourth stage at 130 m³ / h, and the fifth stage at 120 m³ / h. The micro-positive pressure in the reactor is uniformly controlled at 0.02 MPa;
[0080] (S2) Prepare an auxiliary plasticizer containing residual free hydrogen chloride;
[0081] The preparation in step (S2) is as follows:
[0082] (S2-1) Control the chlorination of low-n-alkane liquid paraffin to obtain chlorinated paraffin product auxiliary plasticizer; the chlorinated paraffin product auxiliary plasticizer in step (S2-1) is chlorinated paraffin-52 with a chlorine content of 50%; the reaction temperature for preparing the auxiliary plasticizer is 80℃, and the reaction endpoint is determined based on the refractive index or density of the auxiliary plasticizer.
[0083] (S2-2) During the reaction process in step (S2-1), the vacuum degree of the negative pressure degassing process is adjusted to -0.08MPa, and the degassing time is controlled to be 30min, so as to retain residual free hydrogen chloride in situ in the auxiliary plasticizer;
[0084] (S3) Take the polymer resin, antioxidant and stabilizer, and add them to the mixing system according to the preset ratio with the ester main plasticizer in step (S1) and the auxiliary plasticizer in step (S2) to obtain a resin mixture; the polymer resin in step (S3) is polyvinyl chloride resin, the stabilizer is calcium zinc composite stabilizer, and the antioxidant is hindered phenolic antioxidant; in step (S3), the polymer resin and stabilizer are first preheated to 60°C under high-speed stirring, and then the ester main plasticizer and auxiliary plasticizer are added;
[0085] (S4) The resin mixture in step (S3) is heated to above the glass transition temperature of the polymer resin. The residual free hydrogen chloride induces the polar end of the amphiphilic semi-esterified oligomer to generate an interfacial anchoring effect, so that the polar end forms a secondary bond network with the co-plasticizer and the functional groups of the polymer resin, and constructs a kinetic self-locking structure in the free volume of the amorphous region of the polymer resin to obtain a green plasticizer resin composition.
[0086] The green plasticizer resin composition comprises the following components in parts by weight.
[0087] 15 parts of ester-based primary plasticizer, 10 parts of secondary plasticizer, 50.5 parts of polymer resin, 0.2 parts of antioxidant, and 2 parts of stabilizer;
[0088] The heating temperature in step (S4) is controlled at 155℃;
[0089] The construction of the kinetic self-locking structure in step (S4) is completed in the extrusion molding equipment. The heating temperature of each zone of the extrusion molding equipment is set at 150°C to trigger the interfacial anchoring of the amphiphilic semi-esterified oligomer while the resin mixture is plasticized.
[0090] The extrusion molding equipment is a co-rotating twin-screw extruder. The screw speed of the co-rotating twin-screw extruder is controlled at 150 r / min. The shear field, combined with residual free hydrogen chloride, causes the amphiphilic semi-esterified oligomers to align at the phase interface of the resin mixture.
[0091] After obtaining the green plasticizer resin composition, the process also includes cooling and granulating the green plasticizer resin composition, sieving and packaging it. The surface oil penetration grade of the obtained green plasticizer resin composition after being placed at 65°C for 180 hours is grade 0.
[0092] Example 2: This example is basically the same as Example 1, except that (S1-1) industrial grease with an inlet temperature of 125°C and methanol are introduced into the reaction system and continuously esterified at 130°C; in step (S1-1), the inlet flow rate of the industrial grease is controlled at 4.5 m³ / s. 3 The methanol inlet flow rate is controlled at 1.2 m³ / h. 3 / h; In step (S1), mass percentage The value is 0.8%; (S1-2) The methanol vapor phase temperature in the reaction system of step (S1-1) is controlled within 140℃ as the esterification depth to terminate, so that the in-situ retained amphiphilic hemiesterified oligomers in the ester main plasticizer account for 0.8% of the total mass of the ester main plasticizer; the flow rate decreases step by step, with the first stage at 180 m³ / h, the second stage at 170 m³ / h, the third stage at 160 m³ / h, the fourth stage at 150 m³ / h, and the fifth stage at 140 m³ / h, and the micro-positive pressure in the reactor is uniformly controlled at 0.05 MPa; the chlorinated paraffin product in step (S2-1) is an auxiliary plasticizer. The chlorinated paraffin-52 has a chlorine content of 54%; the reaction temperature for preparing the auxiliary plasticizer is 103℃, and the reaction endpoint is determined based on the refractive index or density of the auxiliary plasticizer; (S2-2) In the reaction process of step (S2-1), the vacuum degree of the negative pressure degassing process is adjusted to -0.05MPa, and the degassing time is controlled to 15min, so as to retain residual free hydrogen chloride in situ in the auxiliary plasticizer; the antioxidant is a phosphite antioxidant; in step (S3), the polymer resin and stabilizer are preheated to 80℃ under high-speed stirring, and then the ester main plasticizer and auxiliary plasticizer are added;
[0093] The green plasticizer resin composition comprises the following components in parts by weight.
[0094] 25 parts of ester-based primary plasticizer, 20 parts of secondary plasticizer, 72.8 parts of polymer resin, 0.5 parts of antioxidant, and 4 parts of stabilizer;
[0095] The heating temperature in step (S4) is controlled at 175℃; the construction of the kinetic self-locking structure in step (S4) is completed in the extrusion molding equipment, and the heating temperature of each zone of the extrusion molding equipment is set at 185℃ to trigger the interfacial anchoring of the amphiphilic semi-esterified oligomers while plasticizing the resin mixture; the extrusion molding equipment is a co-rotating twin-screw extruder, and the screw speed of the co-rotating twin-screw extruder is controlled at 300r / min. The shear field is used in conjunction with residual free hydrogen chloride to make the amphiphilic semi-esterified oligomers oriented and aligned at the phase interface of the resin mixture; the surface oil penetration grade of the green plasticizer resin composition after being placed at 75℃ for 150h is grade 0.
[0096] Example 3: This example is basically the same as Example 1, except that (S1-1) industrial grease with an inlet temperature of 118°C and methanol are introduced into the reaction system and continuously esterified at 115°C; the inlet flow rate of the industrial grease is controlled at 3.7m. 3 The methanol inlet flow rate is controlled at 0.9 m³ / h. 3 / h; In step (S1-1), the methanol vapor phase temperature in the reaction system is controlled at 125℃ as the esterification depth to terminate, ensuring that the in-situ retained amphiphilic hemiesterified oligomers in the ester main plasticizer account for 0.3% of the total mass of the ester main plasticizer; the flow rate decreases gradually in stages: stage 1 is 165 m³ / h, stage 2 is 155 m³ / h, stage 3 is 145 m³ / h, stage 4 is 135 m³ / h, and stage 5 is 125 m³ / h, with the micro-positive pressure inside the reactor uniformly controlled at 0.03 M. Pa; the chlorinated paraffin product co-plasticizer in step (S2-1) is chlorinated paraffin-52 with a chlorine content of 51%; the reaction temperature during the preparation of the co-plasticizer is 85℃; during the reaction process in step (S2-1), the vacuum degree of the negative pressure degassing process is adjusted to -0.07MPa, and the degassing time is controlled to 25min, so as to retain residual free hydrogen chloride in situ in the co-plasticizer; the polymer resin and stabilizer are preheated to 65℃ under high-speed stirring.
[0097] The green plasticizer resin composition comprises the following components in parts by weight.
[0098] 18 parts of ester-based primary plasticizer, 12 parts of secondary plasticizer, 55 parts of polymer resin, 0.3 parts of antioxidant, and 2.5 parts of stabilizer;
[0099] The heating temperature in step (S4) is controlled at 160℃; the heating temperature of each zone of the extrusion molding equipment is set at 155℃; the screw speed of the co-rotating twin-screw extruder is controlled at 200r / min; the surface oil penetration grade of the green plasticizer resin composition after being placed at 68℃ for 170h is grade 0.
[0100] Example 4: This example is basically the same as Example 1, except that (S1-1) industrial grease with an inlet temperature of 123°C and methanol are introduced into the reaction system and continuously esterified at 125°C; the inlet flow rate of the industrial grease is controlled at 4.2 m³ / s. 3 The methanol inlet flow rate is controlled at 1.1 m³ / h. 3 / h; (S1-2) Controlling the methanol vapor phase temperature in the reaction system within the range of 135℃ in step (S1-1) is used as the esterification depth to terminate the reaction, ensuring that the in-situ retained amphiphilic hemiesterified oligomers in the ester main plasticizer account for 0.7% of the total mass of the ester main plasticizer; the rate decreases stepwise: 175 m³ / h for stage 1, 165 m³ / h for stage 2, 155 m³ / h for stage 3, 145 m³ / h for stage 4, and 135 m³ / h for stage 5, with the micro-positive pressure in the reactor uniformly controlled at 0.04 MPa; Step (S2-1) The chlorinated paraffin product used as an auxiliary plasticizer is chlorinated paraffin-52 with a chlorine content in the range of 53%; the reaction temperature during the preparation of the auxiliary plasticizer is 100℃; (S2-2) in the reaction process of step (S2-1), the vacuum degree of the negative pressure degassing process is adjusted to -0.06MPa and the degassing time is controlled to 20min, so as to retain residual free hydrogen chloride in situ in the auxiliary plasticizer; the antioxidant is a phosphite antioxidant; in step (S3), the polymer resin and stabilizer are preheated to 75℃ under high-speed stirring;
[0101] The green plasticizer resin composition comprises the following components in parts by weight.
[0102] 22 parts of ester-based primary plasticizer, 18 parts of secondary plasticizer, 70 parts of polymer resin, 0.4 parts of antioxidant, and 3.5 parts of stabilizer;
[0103] The heating temperature in step (S4) is controlled at 170℃; the heating temperature of each zone of the extrusion molding equipment is set at 180℃; the screw speed of the co-rotating twin-screw extruder is controlled at 250 r / min; the surface oil penetration grade of the green plasticizer resin composition after being placed at 72℃ for 160 h is grade 0.
[0104] Example 5: This example is basically the same as Example 1, except that (S1-1) industrial grease with an inlet temperature of 120°C and methanol are introduced into the reaction system and continuously esterified at 120°C; the inlet flow rate of the industrial grease is controlled to be 4m³. 3 / h, control the methanol inlet flow rate to 1m³ / h. 3 / h; (S1-2) Control step (S1-1) The methanol vapor phase temperature in the reaction system is controlled at 130℃ as the esterification depth to stop, so that the in-situ retained amphiphilic hemiesterified oligomers in the ester main plasticizer account for 0.5% of the total mass of the ester main plasticizer; the flow rate decreases stepwise, first stage is 170 m³ / h, second stage is 160 m³ / h, third stage is 150 m³ / h, fourth stage is 140 m³ / h, and fifth stage is 130 m³ / h, and the micro-positive pressure in the reactor is uniformly controlled at 0.035 MPa; Step The chlorinated paraffin product co-plasticizer in (S2-1) is chlorinated paraffin-52 with a chlorine content in the range of 52%; the reaction temperature during the preparation of the co-plasticizer is 95℃; (S2-2) in the reaction process of step (S2-1), the vacuum degree of the negative pressure degassing process is adjusted to -0.065MPa and the degassing time is controlled to 23min, so as to retain residual free hydrogen chloride in the co-plasticizer in situ; in step (S3), the polymer resin and stabilizer are preheated to 70℃ under high-speed stirring.
[0105] The green plasticizer resin composition comprises the following components in parts by weight.
[0106] 20 parts of ester-based primary plasticizer, 15 parts of secondary plasticizer, 62 parts of polymer resin, 0.35 parts of antioxidant, and 3 parts of stabilizer;
[0107] The heating temperature in step (S4) is controlled at 165℃; the heating temperature of each zone of the extrusion molding equipment is set at 165℃; the screw speed of the co-rotating twin-screw extruder is controlled at 220r / min; the surface oil penetration grade of the green plasticizer resin composition after being placed at 70℃ for 168h is grade 0.
[0108] Example 6: In the production scenario of PVC power cable sheath material, the material needs to operate in an outdoor environment with drastic temperature fluctuations. The composite plasticizer system composed of fatty acid methyl esters and chlorinated paraffin-52 undergoes phase separation. When the ambient temperature fluctuates with diurnal cycles, the polarity difference causes thermodynamically driven differential migration of fatty acid methyl ester molecules and chlorinated paraffin long chains within the PVC matrix, leading to oil seepage and precipitation on the cable surface, accompanied by material hardening and weakening the protective performance of the sheath material. In preparing the ester-based main plasticizer, industrial oil with an acid value greater than 2 is selected as the raw material. The oil inlet temperature is controlled at 115℃~125℃. The industrial oil and methanol enter five esterification reactors connected in series for a continuous esterification reaction. The methanol vapor phase temperature is maintained at 120℃~140℃. The reaction is stopped at a specific esterification conversion rate, so that 0.5% of the total mass of amphiphilic semi-esterified oligomers with polar hydroxyl ends and long-chain aliphatic hydrocarbon ends are retained in the obtained ester main plasticizer. During esterification, the system continuously monitors the change in refractive index of the reaction mixture through an online refractometer to characterize the instantaneous state of micro-polymerization degree. Once the mass percentage calculated from the refractive index signal reaches the preset target range of 0.2%~0.8%, the control center triggers the forced cooling circuit, injects high-throughput coolant into the jacket, and lowers the temperature inside the reactor to below the reaction activity threshold in a very short time, thereby establishing a negative feedback execution loop of macro-temperature control and micro-retention depth.
[0109] In the preparation of the auxiliary plasticizer, low-n-alkane liquid paraffin was introduced into the chlorination reaction system, and chlorination was continuously carried out at a temperature of 90℃~103℃ until the chlorine content of the product reached 52%. The vacuum degree of the negative pressure degassing process was adjusted to -0.06MPa and maintained for 20min to retain residual free HCl inside the auxiliary plasticizer. The mixture consisted of 65 parts polyvinyl chloride resin, 20 parts ester-based main plasticizer containing amphiphilic semi-esterified oligomers, 15 parts auxiliary plasticizer containing residual free HCl, 0.3 parts antioxidant, and 3... A calcium-zinc composite stabilizer was added to a high-speed mixer and mixed. The resulting resin mixture was then fed into a co-rotating twin-screw extruder. The extruder temperature was controlled at 165°C, which is higher than the glass transition temperature of polyvinyl chloride (PVC) resin. The molten PVC resin segments underwent movement, and residual free HCl distributed in the liquid phase micro-regions induced orientation polarization at the polar ends of the amphiphilic semi-esterified oligomers. Hydrogen bonds and dipoles formed between the polar ends of the amphiphilic semi-esterified oligomers and the chlorine-rich segments in the auxiliary plasticizer and the functional groups of the PVC resin. An interaction network exists where the nonpolar long chains of amphiphilic semi-esterified oligomers interweave and entangle within the free volume of the amorphous regions of PVC resin, constructing a kinetically self-locking structure at the interface. Because the residual free hydrogen chloride trapped in the co-plasticizer is only in trace amounts at the part-per-million level and is spatially isolated and encapsulated by the long-chain alkane microdomains of the oligomers, the free acid is insufficient to trigger a macroscopic dehydrochlorination degradation reaction in the PVC macromolecular chain within a thermodynamic field of 165°C. The confined free protons, with their strong electronegativity, act as local polar... The core of the process, before the heat stabilizer fully performs its neutralization action, preemptively activates the instantaneous dipole moment of the oligomer end groups with a time constant in the microsecond range, converting the degradation potential energy into the driving force for the assembly of the secondary bond network at the catalytic interface. The resulting green plasticizer resin composition undergoes an aging test at 70°C for 168 hours, and its surface oil penetration level is 0. The interaction between the amphiphilic semi-esterified oligomer and the residual free HCl counteracts the migration potential energy of the plasticizer molecules, blocks the differential thermodynamic migration of the plasticizer molecules, and solves the oil penetration defect on the surface of the composition.
[0110] Example 7: In this example, the compatibility stability of the green plasticizer resin composition and the boundary effect verification of its preparation method were carried out using a physical experimental platform equipped with a programmable heating oven and an electronic balance with an accuracy of 0.01 mg. The thermal stress fluctuation of the power cable sheath material under the diurnal temperature difference was simulated. The mass loss rate of plasticizer molecules was evaluated by thermo-oxidative accelerated aging at 70°C for 168 hours. The heating temperature of the mixing system was set at 165°C. This set value was determined based on the glass transition temperature range of polyvinyl chloride resin from 80°C to 85°C, and was used to balance the energy supply required for the movement of polyvinyl chloride resin chains with the risk of thermal degradation.
[0111] A comparative system was established comprising sample group 1 of the present invention, control sample group 1, and control sample group 2. Sample group 1 of the present invention used an ester-based primary plasticizer containing 0.5% by mass of an amphiphilic hemiesterified oligomer, and an auxiliary plasticizer containing residual free HCl in situ. The residual free HCl was locked by controlling the vacuum degree of the negative pressure degassing process to -0.06 MPa and maintaining it for 20 minutes. Control sample group 1 did not contain the amphiphilic hemiesterified oligomer. Control sample group 2 used a sample that had undergone degassing at a vacuum degree of -0.1 MPa for 60 minutes. To simulate the fluctuations in operating conditions caused by heater performance drift in real industrial production, an auxiliary plasticizer was actively introduced with a temperature disturbance of ±2°C during the blending and extrusion stage. Test data showed that the aging mass loss rate of sample group one was 0.12%, and the surface oil penetration level was 0. The mass loss rate of control sample group one was 1.85%, with oil stains appearing on the surface. The mass loss rate of control sample group two was 1.42%. The data confirmed that residual free HCl induced the amphiphilic semi-esterified oligomers to produce an interfacial anchoring effect, thereby inhibiting the differential migration of plasticizers.
[0112] As shown in Table 1, gradient experimental groups were established based on the mass percentage of amphiphilic semi-esterified oligomers, using sample groups with mass percentages of 0.2%, 0.5%, and 0.8%, respectively. A control group with a mass percentage of 0.1% (below the lower limit) and a control group with a mass percentage of 1.0% (below the upper limit) were also set up. The measured data showed that when the mass percentage of amphiphilic semi-esterified oligomers increased from 0.2% to 0.8%, the aging mass loss rate decreased non-linearly from 0.45% to 0.09%. When the mass percentage further increased to 1.0%, the mass loss rate was 0.08%, and the performance gain trend tended to level off and showed a saturation inflection point. This phenomenon indicates that polyvinyl chloride resin... The limited free volume and near-saturation of reaction sites within the amorphous region of the ester confirm that a mass percentage range of 0.2% to 0.8% is the optimal range for balancing compatibility improvement and processing efficiency. The experimental data system confirms the effectiveness of this preparation method in addressing the imbalance of plasticizer polarity gradient. By in-situ retaining a specific concentration of amphiphilic semi-esterified oligomers and residual free HCl, the two are used to synergistically construct a kinetic self-locking structure, enabling the green plasticizer resin composition to maintain uniform component distribution under complex service environments, blocking the differential thermodynamic migration of ester-based primary plasticizers and auxiliary plasticizers, and solving the defects of precipitation and oil seepage on the surface of the composition.
[0113] Table 1: Complete Performance Table of Gradient Controls
[0114]
[0115] A free hydrogen chloride concentration gradient control group was set up. The content of semi-esterified oligomer was controlled at 0.5 wt%, the main plasticizer was 20 parts, the auxiliary plasticizer was 15 parts, the extrusion temperature was 165℃ and the screw speed was 220 r / min. Only the degassing vacuum degree and degassing time of chlorinated paraffin were adjusted to obtain samples with different free HCl contents. 1 mm thick 50×50 mm sheets were uniformly prepared. Simultaneously, 70℃ and 168h heat aging tests were carried out to detect oil seepage, aging mass loss, sheet yellowing index and melt flow rate (MFI). The test results are shown in Table 2.
[0116] Table 2: Results of Free Hydrogen Chloride Concentration Gradient Test
[0117]
[0118] The results show that when free HCl is below 45 ppm, there is a lack of sufficient polarization induction medium, and a complete kinetic self-locking network cannot be formed, resulting in a large amount of plasticizer migration and oil seepage. When it is above 55 ppm, excessive free HCl will catalyze the dehydrochlorination degradation of PVC at high extrusion temperatures, causing the product to turn yellow. Only the range of 45-55 ppm can simultaneously take into account both excellent anti-migration performance and PVC thermal stability, proving that this retention range is necessary and optimal.
[0119] An extrusion plasticizing temperature gradient control test group was set up. The oligomer content was controlled at 0.5 wt%, HCl at 50 ppm, and screw speed at 220 r / min. Only the temperature of each zone of the extruder was adjusted. After granulation and flake preparation with the same formula, the interface molding effect, oil penetration, rheology and thermal aging properties were tested. The results are shown in Table 3.
[0120] Table 3: Results of Extrusion Plasticizing Temperature Gradient Test
[0121]
[0122] The results showed that when the extrusion temperature was below 155℃, the PVC chain segments lacked mobility, free HCl could not drive the amphiphilic oligomers to orient themselves towards the phase interface, the kinetic self-locking structure could not be constructed, and plasticizers precipitated and leaked oil. Temperatures above 175℃ easily caused the oligomers to thermally decompose and the PVC to thermally degrade and turn yellow. Only in the range of 155-175℃ could a stable self-locking network be formed completely, taking into account processing fluidity, oil resistance and material thermal stability. Among them, 160-170℃ was the optimal range for comprehensive performance.
[0123] Example 8: This example combines Figures 1 to 2 The preparation method of the green plasticizer resin composition is described, such as... Figure 1As shown, step (S1) involves preparing an ester-based primary plasticizer containing amphiphilic semi-esterified oligomers. This is achieved by continuously esterifying industrial oil with methanol at 110°C to 130°C, controlling the inlet temperature to be 115°C to 125°C, and stopping the esterification depth by controlling the methanol vapor phase temperature within the system to be within the range of 120°C to 140°C. This results in 0.2% to 0.8% of the amphiphilic semi-esterified oligomers by mass being retained in situ in the primary plasticizer. Step S2 involves preparing a secondary plasticizer containing residual free hydrogen chloride. This is achieved by controlling the chlorination of low-n-alkane liquid paraffin to obtain a chlorinated paraffin product, and adjusting the vacuum degree of the negative pressure degassing process to -0.08 MPa to -0.0 MPa. At 5 MPa, the degassing time is controlled to be 15 min to 30 min to retain residual free hydrogen chloride in situ in the co-plasticizer. In step (S3), the polymer resin, ester-based main plasticizer, and co-plasticizer are added to the mixing system according to a preset ratio to obtain a resin mixture. In step (S4), the resin mixture is heated to above the glass transition temperature of the polymer resin. The residual free hydrogen chloride induces the polar end of the amphiphilic semi-esterified oligomer to generate an interfacial anchoring effect, so that the polar end forms a secondary bond network with the functional groups of the co-plasticizer and polymer resin, and constructs a kinetic self-locking structure in the free volume of the amorphous region to obtain a green plasticizer resin composition.
[0124] like Figure 2 As shown, the overall system consists of a raw material and reaction medium supply cluster, an in-situ preparation and endogenous component generation node, a composite transformation and structure locking center, and a finished product output and quality calibration layer. On the raw material supply side, it involves industrial oils with an acid value greater than 2, methanol gaseous medium, low-n-alkane liquid paraffin, and polyvinyl chloride resin as a polymer resin. The in-situ preparation stage includes a continuous esterification reaction system consisting of five esterification reactors connected in series, used to retain in-situ 0.2%-0.8% of amphiphilic topological pinning medium, i.e., amphiphilic semi-esterified oligomers. The polymer also includes a chlorination degassing control system in a vacuum negative pressure process with a negative pressure range of -0.08MPa to -0.05MPa, used to retain residual free hydrogen chloride as a polarization catalyst in situ; the composite conversion stage integrates a high-speed mixing system and a co-rotating twin-screw extruder, the latter constructing a phase interface reconstruction field to perform the task of kinetic self-locking structure construction, specifically including triggering interface anchoring, forming a secondary bond network, and establishing a physical entanglement network; the final output is a green plasticizer resin composition with a surface oil penetration level of 0.
[0125] Example 9: In the production of high-flexibility PVC medical catheters, the tubing needs to meet the requirements of 121℃ saturated steam sterilization and long-term contact with biological fluids. Traditional composite plasticizing systems, under high-temperature and humid conditions, experience interfacial desorption due to their low compatibility barrier, leading to white, hazy oil precipitation on the tubing surface, causing transparency degradation and biosafety risks. By precisely calibrating the concentration of endogenous components and controlling their polarization at the interface, a kinetic self-locking structure is constructed to resist the disruption of the plasticizing component's balance by the external energy field. In the preparation of the ester-based main plasticizer, soybean oil with an acid value of 2.5 is selected as the raw material, and the oil inlet temperature is set at 120℃. The soybean oil and methanol are mixed at a 4m... 3 / h and 1m 3 A flow rate of [value] / h is fed into an esterification reaction system equipped with an online Abbe refractometer, which monitors the online refractive index of the reaction mixture in real time. Determining the depth of esterification, including refractive index The target value was determined based on gradient experiments using amphiphilic hemiesterified oligomer concentrations, when detected... When the concentration is in the range of 1.445 to 1.448, the instantaneous mass percentage of the amphiphilic semi-esterified oligomer is determined to be 0.65%. At this point, the reaction is terminated by reducing the heating load of the reactor to cool the system from 130°C to 105°C, thereby locking in the preset concentration of the topological pinning medium.
[0126] In the preparation of the auxiliary plasticizer, a physical correlation model was established between the concentration of residual free HCl and the intensity of negative pressure degassing. The chlorine content of the liquid paraffin chlorination product was controlled at 52%. The degassing vacuum was limited to -0.055MPa to -0.065MPa using a vacuum pressure sensor, and the degassing time was maintained for 20 minutes. The mass concentration of residual free HCl in the degassed auxiliary plasticizer was determined by silver nitrate potentiometric titration. When the measured value was between 45ppm and 55ppm, this concentration served as a charge compensation source for inducing interfacial orientation polarization, supporting the in-situ formation of subsequent self-locking structures. The underlying logic of the physical correlation model is based on the gas-liquid phase equilibrium equation and the mass transfer law. The mass transfer resistance coefficient and gas diffusion constant of the liquid paraffin at the current viscosity grade were pre-entered into the model calculation process. By inversely solving for the maximum exhaust pressure difference necessary to overcome the liquid film tension, the absolute negative pressure operating domain corresponding to the specific concentration target was derived, ensuring that the process control commands achieve quantitative engineering traceability. 65 parts of polyvinyl chloride resin and 22 parts of amphiphilic semi-esterified oligomers were used. An ester-based primary plasticizer, 14 parts of an auxiliary plasticizer containing residual free HCl, 0.4 parts of an antioxidant, and 3.5 parts of a stabilizer were added to a mixing system. The resulting mixture was fed into a co-rotating twin-screw extruder and gradually heated to 168°C. The residual free HCl distributed within the system synergistically induced orientation polarization at the polar ends of the amphiphilic semi-esterified oligomers. This polar end then interacted with the chlorine-rich microregions in the auxiliary plasticizer and the functional groups of the polyvinyl chloride resin, forming a high-density hydrogen bond network. The non-polar long chains of the amphiphilic semi-esterified oligomers... The polymer forms physical cross-entanglement with the segments of polyvinyl chloride resin, constructing a kinetic self-locking structure in situ within the free volume of the amorphous region of the resin. After sterilization at 121°C for 30 min, the resulting green plasticizer resin composition has a light transmittance of 89.2%. After soaking in physiological saline at 37°C for 240 h, no plasticizer precipitation was detected. The self-locking structure constructed at the interface between the amphiphilic semi-esterified oligomer and residual free HCl counteracts the diffusion dynamics caused by thermal stress and chemical dissolution, achieving component stability of the polymer composition in the field of medical devices.
[0127] Example 10: This example addresses the situation where the acid value and fatty acid composition of industrial oils fluctuate with different supply batches. The retention limit of amphiphilic semi-esterified oligomers is determined using a feed-related refractive index calibration method. For each batch of raw oil, 10 kg of sample is drawn into the pilot-scale esterification reactor, and the refractive index of the reaction solution is collected every 5 minutes. and the corresponding measured mass percentage of amphiphilic hemiesterified oligomers, fitted refractive index Mass ratio of amphiphilic hemiesterified oligomers The linear mapping function is used to determine the target refractive index corresponding to a 0.5% cutoff based on the response curve of the current batch of feedstock oil. and the Input to the production line control system; during the preparation of the main plasticizer, when the online refractive index monitoring value reaches... The cooling feedback loop is activated to lower the system temperature below 105°C within 2 minutes, thus halting the esterification reaction; the online refractive index reaches the target refractive index. At that time, turn on the jacket cooling water, with the circulating cooling water temperature at 20-30℃ and the flow rate at ≥5m³ / h. Within 2 minutes, reduce the reactor temperature from 130℃ to ≤105℃ to terminate the transesterification reaction and lock in the oligomer content.
[0128] To address the differences in diffusion resistance arising from batch changes in low-n-alkane liquid paraffin raw materials, the cutoff window for residual free HCl was determined using a vacuum gradient calibration method. A crude auxiliary plasticizer with a chlorine content of 52% was divided into three groups, and degassing pressures of -0.05 MPa, -0.06 MPa, and -0.07 MPa were applied and maintained for 20 min, respectively. The mass concentration of residual free HCl in each group was determined using silver nitrate potentiometric titration. The vacuum pump speed was adjusted based on the deviation of the measured concentration from the 45 ppm to 55 ppm range to compensate for the diffusion resistance of paraffin components of different viscosity grades under negative pressure. The resulting auxiliary plasticizer and main plasticizer... When plasticizers are added to polyvinyl chloride resin, the resulting composition, when subjected to an external shear field, exhibits amphiphilic semi-esterified oligomers that combine with residual free HCl to form a physically entangled network structure. This achieves a stable distribution of the plasticizer components within the resin. In this evolution mechanism, the macroscopic high-shear flow field forces the amorphous matrix chain segments to disentangle through strong axial and radial stretching, opening up sufficient transient free volume for the penetration of polarized molecules. When the melt flows towards the die, causing a sharp decrease in the shear strain rate, the spatially rearranged microscopic molecular groups rapidly lock their conformation within the stress relaxation window using hydrogen bonding, completing the dissipation transition of destructive kinetic energy into a microscopic steady-state network.
[0129] Example 11: In this example, for pre-production calibration scenarios adapted to batches of industrial oil raw materials from different origins, an offline calibration matrix is established to determine the mapping benchmark between refractive index and component concentration. A 10kg sample is extracted from the current batch of raw oil and fed into a pilot-scale esterification device. The reaction is carried out continuously at a temperature of 120℃ and a pressure of 0.1MPa, and the refractive index of the mixture is collected every 5 minutes. Readings were taken, and the mass percentage of the amphiphilic hemiesterified oligomers was determined simultaneously using liquid chromatography. A linear equation was derived by fitting the obtained 10 sets of related data points. ,in, The fitted slope, The intercept is used; the target refractive index corresponding to a mass percentage of 0.5% is calculated based on the equation. ,in, The target refractive index is set, and this target value is input into the controller of the main plasticizer production line. When the online monitoring signal arrives... The cooling feedback loop is activated at that time.
[0130] When the system encounters conditions where fluctuations in ambient atmospheric pressure cause a shift in the degassing efficiency of the auxiliary plasticizer, feedback regulation logic is used to maintain the stability of the load of residual free HCl inside the auxiliary plasticizer. During the degassing process, fluid samples of the auxiliary plasticizer are collected every 15 minutes, and the measured mass concentration of residual free HCl is determined using a silver nitrate potentiometric titrator. The controller retrieves a preset threshold range of 45ppm to 55ppm as the judgment benchmark and calculates the deviation between the measured concentration and the target median of 50ppm. ,in, For concentration deviation; if If the fluctuation exceeds the preset range of ±5ppm, then according to The frequency of the vacuum pump motor is adjusted in both positive and negative directions to compensate for the degassing resistance of the paraffin component under different pressure fields by changing the absolute pressure value of the negative pressure process. The auxiliary plasticizer and the main plasticizer are added together to polyvinyl chloride resin. The resulting green plasticizer resin composition maintains a consistent surface oil resistance rating in different production batches.
[0131] In the thermal history calibration conditions used to establish the construction quality of the kinetic self-locking structure, the specific heat capacity of the resin composition during the condensation process is measured. The cooling rate window was determined by the change curve. The melt sample leaving the extrusion die was cooled at three gradients of 10℃ / min, 20℃ / min, and 30℃ / min using a differential scanning calorimeter. The evolution of the exothermic peak morphology within the glass transition temperature range of polyvinyl chloride resin was monitored, and the free volume shrinkage rate of the amorphous region under different cooling rates was calculated. When the cooling rate was controlled at 20℃ / min, the dipole interaction points formed by the amphiphilic semi-esterified oligomer segments and residual free HCl in the system completed spatial rearrangement before the amorphous region segments were frozen. The resulting green plasticizer resin composition showed no grease-like component migration on the surface after aging at 70℃ for 168h. The experimental data confirmed that this thermal history condition was conducive to the formation of a physical entanglement and chemical anchoring coupling network in the three-dimensional space of the resin matrix.
[0132] Example 12: This example addresses the background optical disturbances in the monitoring of trace component concentrations and the chemical competition properties between different additives within the composite system under large-scale continuous blending conditions. It constructs an online baseline compensation and extrusion spatiotemporal decoupling procedure. Based on the Lorentz-Lorentz optical correlation mechanism, the overall refractive characteristics of the reaction medium are jointly determined by the molar refractive index and density difference of each component. The measurement and control system synchronously and continuously collects the reference refractive index of the currently produced batch of pure industrial oils that have not undergone esterification. and the real-time absolute refractive index of the reaction mixture in the esterification reactor The relative change in refractive index is obtained by calculating the difference between the two. The control unit selects the relative refractive index change. Instead of using the conventional single-point absolute refractive index as the closed-loop trigger signal for the termination reaction, differential operations are used to filter out optical substrate drift interference introduced by crude oil origin replacement and system thermal fluctuations. This ensures that the quantitative monitoring trajectory of oligomer retention concentration is uniquely mapped to the esterification conversion rate. A kinetic self-locking structure construction procedure is executed, and a multi-stage physically isolated temperature zone is established sequentially along the material feed direction using a co-rotating twin-screw extruder. The front end of the extruder is set as the main and auxiliary plasticizer injection section, with the temperature controlled at 90℃~110℃. This guides the pre-plasticization of PVC resin and auxiliary plasticizers containing residual free hydrogen chloride (including oligomer esters) within this low-viscosity temperature zone. The abundant free volume and relatively low steric hindrance released when PVC segments cross the glass transition temperature allow free hydrogen chloride gas molecules to... A sufficient time constant guides the polar ends of the amphiphilic semi-esterified oligomers to establish microscopic orientation; the middle and rear ends of the extruder are designated as the plasticizing and neutralizing section, with the temperature controlled to rise to 165℃~175℃, and a separate downstream feed port is set up to quantitatively add calcium-zinc composite stabilizer; the length-to-diameter ratio of the co-rotating twin screw is L / D=40~44; a melt sealing zone is set between the pre-plasticizing section and the plasticizing and neutralizing section, with a length accounting for 1 / 8 of the total screw length; three sets of reverse kneading blocks and four dense flow-blocking rings are set in the sealing zone, with a single-sided gap of 0.1~0.15mm between the flow-blocking rings and the barrel; the local screw compression ratio in the sealing zone is 3.2~3.5, forming a high-pressure melt barrier to prevent the downstream calcium-zinc stabilizer from flowing back to the front pre-plasticizing section, ensuring that free HCl first completes the oligomer polarization and anchoring before neutralization and deacidification.
[0133] To effectively implement the aforementioned spatiotemporal physical isolation and decoupling during extrusion, the co-rotating twin-screw extruder is equipped with a dedicated melt sealing zone at the junction of the pre-plasticizing section and the plasticizing neutralization section. This zone consists of alternating stacks of reverse kneading blocks and dense flow-blocking rings. The specific mechanical screw configuration creates a high-pressure sealing blockage by locally compressing the material, establishing a dynamic sealing barrier. This prevents the calcium-zinc composite stabilizer introduced from the downstream side from flowing back and leaking into the front polarization reaction temperature zone. The screw's axial length-to-diameter ratio provides a physical spatial barrier, blocking the premature neutralization and consumption reaction of the calcium-zinc composite stabilizer, which is a halogen absorber, on free hydrogen chloride gas. In terms of process timing, the polarization induction action takes precedence over the deacidification and dehalogenation action of the heat stabilizer, ultimately locking in the dynamic morphology of the uniformly dispersed interface inside the multiphase material.
[0134] The embodiments of this application have been described above with reference to the accompanying drawings. Unless otherwise specified, the embodiments and features in the embodiments of this application can be combined with each other. This application is not limited to the specific embodiments described above. The specific embodiments described above are merely illustrative and not restrictive. Those skilled in the art can make many other forms under the guidance of this application without departing from the spirit of this application and the scope of protection of this invention, and all of these forms are within the protection scope of this application.
Claims
1. A method for preparing a green plasticizer resin composition, characterized by: Including the following step, (S1) Prepare an ester-based main plasticizer containing amphiphilic semi-esterified oligomers; The preparation in step (S1) is as follows: (S1-1) Industrial oil with an inlet temperature controlled at 115℃~125℃ is introduced into the reaction system with methanol and continuously esterified at a temperature of 110℃~130℃. (S1-2) Controlling the methanol vapor phase temperature in the reaction system within the range of 120℃ to 140℃ in step (S1-1) as the esterification depth to be terminated, so that the in-situ retained amphiphilic hemiesterified oligomers in the ester main plasticizer account for 0.2% to 0.8% of the total mass of the ester main plasticizer; (S2) Prepare an auxiliary plasticizer containing residual free hydrogen chloride; (S3) Take polymer resin, antioxidant and stabilizer, and mix them with the ester main plasticizer in step (S1) and the auxiliary plasticizer in step (S2) in a preset ratio into the mixing system to obtain resin mixture; (S4) The resin mixture in step (S3) is heated to above the glass transition temperature of the polymer resin. The residual free hydrogen chloride induces the polar end of the amphiphilic semi-esterified oligomer to generate an interfacial anchoring effect, so that the polar end forms a secondary bond network with the co-plasticizer and the functional groups of the polymer resin, and constructs a kinetic self-locking structure in the free volume of the amorphous region of the polymer resin, thus obtaining a green plasticizer resin composition.
2. The method for preparing the green plasticizer resin composition according to claim 1, characterized in that: In step (S1-1), the inlet flow rate of the industrial grease is controlled to be 3.5m. 3 / h~4.5m 3 / h, control the methanol inlet flow rate to 0.8m 3 / h~1.2m 3 / h.
3. The method for preparing the green plasticizer resin composition according to claim 1, characterized in that: The steps (S1-2) involve continuous esterification in five esterification reactors connected in series. The concentration stability of the amphiphilic semi-esterified oligomers in the ester main plasticizer is maintained by adjusting the methanol gas flow rate and methanol gas pressure in each esterification reactor.
4. The method for preparing the green plasticizer resin composition according to claim 3, characterized in that: In step (S1-2), the methanol gas flow rate is distributed in a gradient across the five esterification reactors connected in series. The methanol gas flow rate decreases sequentially from the first to the fifth esterification reactor: 160–180 m³ / h for the first stage, 150–170 m³ / h for the second stage, 140–160 m³ / h for the third stage, 130–150 m³ / h for the fourth stage, and 120–140 m³ / h for the fifth stage. The positive pressure inside the reactors is uniformly controlled between 0.02 and 0.05 MPa.
5. The method for preparing the green plasticizer resin composition according to claim 1, characterized in that: In step (S1), the mass percentage of the amphiphilic hemiesterified oligomer in the ester-based main plasticizer satisfies the formula... ,in, This represents the mass percentage of the amphiphilic hemiesterified oligomer. The mass of the amphiphilic semi-esterified oligomer in the system, This represents the total mass of the ester-based primary plasticizer after esterification, expressed as a percentage by mass. The value range is 0.2% to 0.8%.
6. The method for preparing the green plasticizer resin composition according to claim 1, characterized in that: The preparation in step (S2) is as follows: (S2-1) Control the chlorination of low-n-alkane liquid paraffin to obtain chlorinated paraffin product auxiliary plasticizer; (S2-2) During the reaction process in step (S2-1), the vacuum degree of the negative pressure degassing process is adjusted to -0.08MPa to -0.05MPa, and the degassing time is controlled to be 15min to 30min, so as to retain residual free hydrogen chloride in situ in the auxiliary plasticizer.
7. The method for preparing the green plasticizer resin composition according to claim 6, characterized in that: The chlorinated paraffin product co-plasticizer in step (S2-1) is chlorinated paraffin-52 with a chlorine content in the range of 50% to 54%; the reaction temperature for preparing the co-plasticizer is 80℃ to 103℃, and the reaction endpoint is determined based on the refractive index or density of the co-plasticizer.
8. The method for preparing the green plasticizer resin composition according to claim 1, characterized in that: The polymer resin used in step (S3) is polyvinyl chloride resin, the stabilizer is calcium-zinc composite stabilizer, and the antioxidant is hindered phenolic antioxidant or phosphite antioxidant. In step (S3), the polymer resin and stabilizer are first preheated to 60°C to 80°C under high-speed stirring, and then the ester-based primary plasticizer and secondary plasticizer are added.
9. The method for preparing the green plasticizer resin composition according to claim 1, characterized in that: The green plasticizer resin composition comprises the following components in parts by weight. The main plasticizer is 15 to 25 parts ester, the auxiliary plasticizer is 10 to 20 parts, the polymer resin is 50.5 to 72.8 parts, the antioxidant is 0.2 to 0.5 parts, and the stabilizer is 2 to 4 parts.
10. The method for preparing the green plasticizer resin composition according to claim 1, characterized in that: The heating temperature in step (S4) is controlled between 155°C and 175°C. The construction of the kinetic self-locking structure in step (S4) is completed in the extrusion molding equipment. The heating temperature of each zone of the extrusion molding equipment is set at 150℃~185℃ to trigger the interfacial anchoring of the amphiphilic semi-esterified oligomer while the resin mixture is plasticized. The extrusion molding equipment is a co-rotating twin-screw extruder. The screw speed of the co-rotating twin-screw extruder is controlled at 150 r / min to 300 r / min. The shear field, combined with residual free hydrogen chloride, causes the amphiphilic semi-esterified oligomers to align at the phase interface of the resin mixture.
Citation Information
Patent Citations
A migration-resistant, environmentally friendly flexible PVC sheathed cable
CN119742111A